Non-Invasif Termometer:Temporal Artery Thermometer(TAT) Terintegrasi dengan Electronic Medical Recordsebagai Peringkat Teratas Metode Pengukuran Suhu pada Bayi dan Anak: Kajian Literatur - Sugiarti Sugiarti (Politeknik Kesehatan Tanjung Karang, 2018)
Fever in children caused the high use of healthcare facilities. The majority of parents (90%) recognized paracetamol as an antipyretic for children, and only 36.7% of parents who receive the antipyretics were prescribed. Excessive parental concern can lead to aggressive practices harmful to children, such as over dosage of antipyretic use. Accurate temperature assessment was important for early detection of fever, nursing clinical decision, medical diagnosis, and the need for specific laboratory tests. TAT is a new innovation and alternative in the field of child nursing as a detector of fever in children. TAT comes in an automatic form connected to the monitor's vital sign, and integrates with electronic medical records, in order to meet the demanding use of advances in electronic medical records on temperature measurements. Comfort, accuracy, sensitivity, and convenience TAT also carries the concept of nursing atraumatic care and Family Centered Care (FCC). Child nurses in Indonesia need to improve service quality by learning new technologies, and applying existing evidence-based.